The roles of carbide and hydride in oxide-supported palladium nanoparticles for alkyne hydrogenation - Tew, Min Wei; Janousch, Markus; Huthwelker, Thomas; van Bokhoven, Jeroen A. (Journal of catalysis, 2011)
Selective and non-selective hydrogenation of 1-pentyne occurs over carbided oxide-supported palladium nanoparticles. Surface poisoning of the palladium carbide-like phase by alkyne is responsible for the constantly high selectivity up to almost 100% conversion. When the reaction became non-selective, the carbide-like structure remained: Full hydrogenation can also occur in the absence of hydride. [Display omitted] ► A palladium carbide-like phase forms when the palladium NPs are exposed to alkyne. ► Partial and full hydrogenation occur over a palladium carbide-like phase. ► Full hydrogenation can also occur in the absence of hydride. ► Poisoning of the carbide-like phase by alkyne led to constantly high selectivity. ► Larger palladium particles are more selective to partial-hydrogenation of 1-pentyne. Particle size affects the activity and selectivity to partial hydrogenation of 1-pentyne over oxide-supported palladium nanoparticles. Larger particles are intrinsically more selective because of the weaker bond strength of 1-pentene. In situ X-ray absorption near edge structure (XANES) at the Pd L 3 edge revealed the formation of a carbide-like phase as soon as the catalyst is exposed to alkyne, irrespective of particle size. The newly formed phase prevented hydride formation. Surface poisoning of the palladium carbide by alkyne is responsible for the constantly high selectivity, up to almost complete conversion. At almost 100% conversion, all catalysts show low selectivity. The lack of significant pentyne adsorption on the surface causes pentene to undergo consecutive reactions, such as isomerization and complete hydrogenation. The structure of the catalyst was that of carbide-like phase and did not change. Palladium hydride did not form under any of the conditions. Exposure of a carbided catalyst to pure hydrogen leads to partial reversal of the structure. Hydride is not essential for complete hydrogenation to occur.